KETERSERAPAN SENYAWA AKTIF TERPILIH EKSTRAK TEPUNG TEMPE KEDELAI HITAM dan UBI JALAR UNGU pada TIKUS MODEL DIABETES MELLITUS TIPE II - Syahron Mahbub Balada (Scripta Biologica, 2018)
Black soybeans and sweet potatoes contain antioxidants that can inhibit cell damage caused by free radicals. The aim of this study was to determine the absorption of selected active compounds (Isoflavones and Anthocyanins) in type II diabetes (DMT2) rat models. Wistar male rats were used as DMT2 models treated with high fat diet (HFD) and Streptozotosin (STZ) injections until the blood glucose levels reached 160 mg/dl. The experiment was carried out by giving extract of fermented black soybean, which is locally called Tempe, and sweet potato for 28 days on 9 Wistar rats. Rats models were divided into 3 treatment groups. Group I was given with the extract of fermented black soybean flour, group II was given with sweet potato extract, and group III was given with the extract of both fermented black soybean and sweet potato extract with 2:2 ratio. The sample of serum, fecal, and mouse urine were analyzed in the laboratory test by the method of High Pressure Liquid Chromatography (HPLC). The result showed that the absorption of Isoflavones and Anthocyanins extracted from fermented black soybeans and sweet potatoes in type II diabetes rat models were high (99,9%). Therefore, fermented black soybeans and sweet potatoes extract can be used as alternative antidiabetic remedy.